Pemberdayaan Ekonomi Bagi Anggota Majelis Taqorrub Ilallah (MTI) Bekasi Melalui Pelatihan Kewirausahaan - Fatoni, Aris; Setiawan, Iwan (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
This entrepreneurship training was given to the Majelis Taqorrub Ilallah (MTI) having address at Jl. Walet No. 101 RT. 06 RW. 02 Mekarsari Kec. Tambun Selatan Kab. Bekasi 17510. This program aims to instill an entrepreneurial mindset as a way of life for MTI members through increasing entrepreneurial knowledge, understanding of the concept and skills. This program consists of four stages: the first stage providing entrepreneurial knowledge through seminar, the second stage interactive dialogue, the third stage challenges and the fourth stage sharing session. The results of program are improving and deepening participants understanding of entrepreneurship, increasing skills and bring together the entrepreneurial potential of participants for collaboration. The output of program is the ability to think in finding business opportunities, skills to create product descriptions for e-commerce, pioneering business cooperation between MTI members. Keywords: entrepreneurial mindset, entrepreneurship, business, online, honesty, partnership